2021
DOI: 10.1038/s41598-021-97166-x
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility and cytokine responses of human neuronal cells to multiple circulating EV-A71 genotypes in India

Abstract: Enterovirus-A71 (EV-A71) associated Hand, foot and mouth disease (HFMD) is a highly contagious viral infection affecting children in Asia–Pacific region and has become a major threat to public health. Although several EV-A71 genotypes (C, D, and G) were isolated in India in recent years, no recognizable outbreak of EV-A71 caused HFMD, Acute Flaccid paralysis (AFP) or encephalitis have been reported so far. It is essential to study the pathogenicity or cell tropism of these Indian isolates in order to understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…The differential ability of EV-A71 and CVA16 to trigger cytokine expression has been reported before by using human enteroids as a cell model 42 . A recent study showed that EV-A71 genotype G, a clinical isolate from AFP patients, was able to induce higher expression of cytokine/chemokine genes than other isolates 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The differential ability of EV-A71 and CVA16 to trigger cytokine expression has been reported before by using human enteroids as a cell model 42 . A recent study showed that EV-A71 genotype G, a clinical isolate from AFP patients, was able to induce higher expression of cytokine/chemokine genes than other isolates 43 .…”
Section: Discussionmentioning
confidence: 99%